Comparison of Intrathecal Levobupivacaine and Levobupivacaine plus Fentanyl for Cesarean Section - Bidikar, Manjunath (Anesth Essays Res, 2017)
AIMS AND OBJECTIVES: The aim of this study is to compare the effects of intrathecal levobupivacaine with levobupivacaine and fentanyl in patients undergoing cesarean section. METHODS: Patients with American Society of Anesthesiologists Physical Status I and II scheduled for cesarean section under spinal anesthesia were randomly allocated with thirty patients each. Group L: levobupivacaine group – thirty patients (10 mg). Group F: levobupivacaine plus fentanyl group – thirty patients (7.5 mg + 12.5 μg). Hemodynamic monitoring, sensory and motor levels, and neonatal Apgar score were noted intraoperatively. The total duration of motor and sensory block, time for rescue analgesia was noted postoperatively. RESULTS: Prolonged duration of postoperative sensory and rescue analgesia was found in Group F – 112.97 ± 19.42, 231.26 ± 10.92 min as compared to Group L – 100.37 ± 10.64, 185.93 ± 11.09 min and duration of motor blockade was prolonged in Group L – 87.83 ± 15.04 min than Group F – 79.20 ± 8.93 min and P < 0.05 was found statistically significant. Apgar scores in both groups were comparable. CONCLUSION: Intrathecal levobupivacaine plus fentanyl prolonged duration of sensory block and rescue analgesia without prolonging motor block which could help in early ambulation.